Paolo Mantegazza e l'Evoluzionismo in Italia Nuova edizione - Pasini, Walter; Chiarelli, Cosimo (Strumenti per la didattica e la ricerca, 2010)
An eclectic figure - a scientist, novelist, anthropologist, politician and man of his time - Paolo Mantegazza (1831-1910) played a leading role in Italian society and the cultural scene of the late nineteenth century, even if historic events then partially eclipsed his memory. The retrieval and valorisation of the legacy of Mantegazza were the focus of the meetings that were held in the main sites connected with his life (Monza, Florence, Lerici) at which academics in different disciplines exchanged notes on various aspects, some even little known, of his multifaceted activity. This book brings together a selection of the most significant works presented on these occasions. They represent pieces in a complex puzzle which brings fully to light the great variety of interests and curiosities of the man, and the profound methodological rigour that guided his entire scientific production and is today the most evident sign of his contemporary relevance.